Adaptive housing mechanisms within resettlement sites: a case study of Ouled M’Barek resettlement program, Kenitra, Morocco - Ouassim Bensouda; Iman Meriem Benkirane; Vincent Becue; Jérémy Cenci (Urban, Planning and Transport Research)
Resettlement programs, integral to the ‘Villes Sans Bidonvilles’ (Cities without Slums) initiative, aim to rehouse populations from informal settlements to serviced allotments. Despite the advocacy for harmonious urban development, they often fail to prevent informal housing production, leading to a process of re-informalization. Against this backdrop, this research explores housing evolution during the re-informalization process, investigating mechanisms driving housing adaptation on resettlement sites and exploring how identified adaptation mechanisms relate to the dynamic adaptations shaping informal settlements. Based on a case study on the Oulad M’barek site in Kenitra, Morocco, the research utilizes various data collection methods, including transect walks, focus groups, surveys, and measurements, with thematic analysis as the primary analysis method. The results highlight parallels between re-informalization processes in resettlement sites and adaptive processes in informal settlements. These similarities manifest through housing form heterogeneity, enabling residents to customize dwellings based on needs and financial capacities, incremental transformation providing flexibility in time and investment, and functional mix underlining the interconnection between housing and residents’ livelihoods. The findings highlight the complementarity of formal and informal dynamics in addressing informal settlements, highlighting the need for flexible policy frameworks that leverage informal processes while preserving formal regulatory principles.